Increasing Teacher Knowledge and Skills in Learning to Play Projects in PAUD - Wahju Dyah Laksmi Wardhani; Syahrul Mubaroq; Misyana Misyana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This service activity aims to improve the competence of ECCE teachers in the implementation of the Independent Curriculum. The launch of the Independent Curriculum in 2022 has an impact on schools to change the learning strategies applied. Project play strategy is a new form of learning implemented in the application of the Independent Curriculum. This difficulty is experienced by partners, because of limited understanding of the implementation of play projects that do not just mean assigning assignments to students. The solution offered is assistance for the construction of knowledge and skills discourse in designing project play activities as an integrative learning process. Mentoring methods include the stages of Identifying Needs, Designing Teaching Modules and Implementing Classes. The activity was carried out in one of the partner kindergartens of the Faculty of Teacher Training and Education, University of Muhammadiyah Jember, attended by 10 teachers. The results of this activity are expected by teachers to be able to compile teaching modules based on the Profil Pelajar Pancasila which are integrated into learning activities based on learning objectives.